A binary and multi-component TM-MOFs@MgH 2 Composite hydrogen storage material and preparation method thereof
By introducing binary and multivariate TM-MOFs@MgH2 composite hydrogen storage materials into magnesium-based hydrogen storage materials, and using multivariate nanomixed catalyst clusters, the problem of poor hydrogen absorption and release kinetic performance of magnesium-based hydrogen storage materials is solved, achieving lower hydrogen absorption and release reaction temperature and higher hydrogen storage efficiency.
Patent Information
- Application Number
- CN202410944779.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-07-15
AI Technical Summary
The hydrogen absorption and release kinetic performance of magnesium-based hydrogen storage materials is poor, and the hydrogen release temperature is high, which limits its practical application. The existing catalyst addition methods have problems such as uneven distribution and poor synergistic catalytic effect.
Binary and multivariate TM-MOFs@MgH2 composite hydrogen storage material is used to synthesize the MOFs material precursor under normal temperature and pressure through the regulation of solvent and synthesis process, and introduce multivariate nanomixed catalyst clusters to achieve micron-scale mixing and uniform distribution of the catalyst.
The synergistic catalytic efficiency of the catalytic system of magnesium-based hydrogen storage materials has been significantly improved, the kinetic performance of hydrogen absorption and release is improved, the temperature of hydrogen absorption and release is reduced, and the practicality of hydrogen storage materials has been improved.
Smart Images

Figure CN118954427B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of novel hydrogen storage materials, and specifically relates to a binary and multi-element TM-MOFs@MgH 2 Composite hydrogen storage material and preparation method thereof. Background Art
[0002] As a clean and efficient energy source, hydrogen energy is widely regarded as an important new energy source in the 21st century because it only produces water and no other pollutants during combustion. Hydrogen has an extremely high energy density, and its combustion calorific value is as high as 142.351 kJ / kg, which is three times that of traditional gasoline. However, the widespread application of hydrogen energy is restricted by its storage technology. At present, hydrogen storage technology mainly includes three methods: gaseous hydrogen storage, liquid hydrogen storage and solid hydrogen storage.
[0003] Gaseous hydrogen storage usually uses high-pressure steel cylinders, but this method has problems such as poor safety and low hydrogen storage density, and the hydrogen storage capacity is only 1wt% (15MPa). Liquid hydrogen storage needs to be carried out at extremely low temperatures, with high energy consumption and high cost. It is mainly used in the aerospace field and has limited civilian value. Solid-state hydrogen storage is considered to be one of the most promising solutions due to its high safety and hydrogen storage density. Metal hydrides, especially magnesium-based hydrogen storage materials, have attracted much attention due to their theoretical hydrogen storage capacity of up to 7.6wt% and excellent reversible hydrogen absorption and desorption performance. However, the hydrogen absorption and desorption kinetics of magnesium-based hydrogen storage materials are poor, and the desorption temperature is as high as 350°C, which limits their practical application. In order to improve the thermal / kinetic properties of magnesium-based hydrogen storage materials, the method of adding catalysts is usually adopted. At present, mechanical ball milling and liquid phase co-precipitation are the two main catalyst addition methods. The mechanical ball milling method has the problems of uneven catalyst distribution and poor synergistic catalytic effect. The liquid phase co-precipitation method is difficult to achieve large-scale industrial production due to the high activity of magnesium and harsh reaction conditions, complex operation, high cost. Summary of the invention
[0004] The purpose of the present invention is to provide a binary and multi-component TM-MOFs@MgH 2 The composite hydrogen storage material and the preparation method thereof can effectively improve the hydrogen storage performance of magnesium-based materials.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A binary and multi-component TM-MOFs@MgH 2 The preparation method of the composite hydrogen storage material comprises the following steps:
[0007] A binary and multi-component TM-MOFs@MgH 2 The preparation method of the composite hydrogen storage material comprises the following steps:
[0008] S1. Preparation of binary and multi-element transition metal TM-MOFs precursors:
[0009] (1) dissolving two or more of nitrate, sulfate, chloride, bromide, phosphate, carbonate or acetate in an ethanol aqueous solution to obtain a metal ion mixed solution;
[0010] (2) dissolving the surfactant in anhydrous ethanol and stirring at 300-1000 rpm for 3 h to obtain solution A;
[0011] (3) the organic ligand is dissolved in deionized water, stirred at 300-1000 rpm for 20-60 min, and a 2 M alkaline solution is added dropwise to adjust the pH value to obtain solution B;
[0012] (4) stirring the mixed solution obtained in step (1) at a speed of 200-800 rpm for 20-60 min to mix evenly to obtain solution C;
[0013] (5) Solution A was added dropwise to solution C at a rate of 5 mL / min, and stirred at 500-800 rpm for 30 min until the reactants were completely mixed to obtain solution D;
[0014] (6) adding solution D dropwise into solution B at a rate of 10 mL / min, stirring at 400-1200 rpm for 6-48 h, collecting the reaction precipitate, washing, centrifuging, and drying to obtain a TM-MOFs precursor;
[0015] S2. Preparation of composite hydrogen storage material: The TM-MOFs precursor obtained in step S1 was pre-milled and MgH 2 Powder materials, ball milling composite, the ball milled mixture powder is placed in a vacuum environment for complete dehydrogenation to obtain binary and multi-component TM-MOFs@MgH 2 Composite hydrogen storage materials.
[0016] Preferably, the binary and multinary transition metals TM in step S1 include but are not limited to two or more of Ni, Fe, Co, Cu, Zn, Ag, La, Mn, Cr, Ti, Pt, Au, W, Cd, Pd, Mo, Ru, Rh, Nb, Zr, Y, Sc, V, Ce, Pr, Sm, Gd, and Nd, and these metals exist in the form of one or more of nitrates, sulfates, chlorides, bromides, phosphates, carbonates, or acetates.
[0017] Preferably, in step (1), two or more of nitrate, sulfate, chloride, bromide, phosphate, carbonate or acetate are dissolved in 10-100 mL of aqueous ethanol solution respectively.
[0018] Further preferably, the mass proportion of anhydrous ethanol in the ethanol aqueous solution is 0-100%.
[0019] Preferably, the surfactant in step (2) of S1 includes one or more of hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, octadecyldimethylhydroxyethylammonium nitrate, and tetrabutylammonium chloride.
[0020] Preferably, the organic ligand in step (3) of S1 includes one or more of trimesic acid, trimesic acid, terephthalic acid, aminoterephthalic acid, and NN-dimethylimidazole.
[0021] Preferably, the alkaline solution in step (3) comprises one or more of NaOH solution, KOH solution and ammonia solution.
[0022] Preferably, in step (3) S1, the pH value of the solution is adjusted to 7.0.
[0023] Preferably, the cleaning centrifugation treatment in step (6) of S1 is: firstly cleaning with 80% by volume ethanol aqueous solution, centrifuging at 8000 rpm, repeating this process 3-5 times, then cleaning with deionized water, centrifuging at 8000 rpm, repeating this process 3-5 times.
[0024] Preferably, the drying treatment in step (6) of S1 is carried out at 80-130° C. for 24-72 h under a vacuum degree not exceeding 50 Pa to obtain a TM-MOFs precursor.
[0025] Preferably, the pre-milling conditions in step S2 are: a rotation speed of 100-200 rpm and a time of 1-4 h.
[0026] Preferably, the ball milling conditions in step S2 are: rotation speed of 150-300 rpm, and time of 4-8 h.
[0027] Preferably, in step S2, the ball-milled mixture powder is placed in a vacuum environment, kept at 150° C. for 3-6 hours, and then heated to 450° C. in a vacuum environment and kept for 2 hours to completely dehydrogenate.
[0028] The present invention also provides binary and multi-component TM-MOFs@MgH prepared by the preparation method. 2 Composite hydrogen storage materials.
[0029] Compared with the prior art, the present invention has the following advantages and technical effects:
[0030] 1. The present invention synthesizes binary and multi-component mixed MOFs material precursors at room temperature and pressure and with mild reagents (deionized water and anhydrous ethanol) by regulating the solvent and the synthesis process design, and regulates the product nucleation rate and the specific aspect ratio morphology structure by adjusting the mixing ratio of deionized water and anhydrous ethanol.
[0031] 2. The present invention introduces binary and multi-component TM-based MOFs material precursors to form multi-component nano-hybrid catalyst clusters in situ during the heating process, achieving micrometer-scale mixing and uniform distribution of catalysts, thereby significantly improving the synergistic catalytic efficiency of the magnesium-based hydrogen storage material catalytic system and improving the system's hydrogen absorption and desorption kinetics. The binary and multi-component TM-MOFs@MgH 2 Compared with pure MgH 2 The hydrogen storage material has a small decrease in hydrogen storage capacity, a significantly reduced temperature for hydrogen absorption and desorption reactions, and greatly improved kinetics, which significantly improves the practicality of the hydrogen storage material.
[0032] 3. Binary and multi-component TM-MOFs@MgH 2 The preparation method of composite hydrogen storage material is different from traditional MgH 2 The preparation process of the multi-component catalytic hydrogen storage material of the present invention is simple in preparation process, has good synergistic catalytic performance of the materials, is highly operable, has a short preparation cycle, and has a high yield rate; the required raw materials are cheap and readily available, the preparation process cost is low, and has high safety, and is suitable for industrial mass production.
[0033] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the SEM image of the ternary TM-MOFs (TM=Fe, Co, Ni) precursor material in Example 1;
[0035] Figure 2 The ternary TM-MOFs@MgH provided in Example 1 2 Composite hydrogen storage material and pure MgH provided in Comparative Example 1 2 XRD spectrum of the material;
[0036] Figure 3 The ternary TM-MOFs@MgH provided in Example 1 2 Automatic PCT curves of composite hydrogen storage materials at different temperatures;
[0037] Figure 4 The ternary TM-MOFs@MgH provided in Example 1 2 DSC curve of composite hydrogen storage material;
[0038] Figure 5 The ternary TM-MOFs@MgH provided in Example 1 2 ln(β / Tp of composite hydrogen storage materials 2 )vs.1000 / T p Fitting plot. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0040] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0041] MgH used in the comparative examples and embodiments of the present invention 2 Materials were purchased from Shanghai Meiyuan Power Technology Co., Ltd. Other test materials are conventional test materials in the field and can be purchased through commercial channels.
[0042] Example 1
[0043] A binary and multi-component TM-MOFs@MgH 2 The preparation method of the composite hydrogen storage material comprises the following steps:
[0044] S1. Preparation of binary and multi-element transition metal TM-MOFs precursors, comprising the following steps:
[0045] (1) 9mmol Ni(NO 3 ) 2 6H 2 O (2.617 g), 6 mmol Fe(NO 3 ) 3 9H 2 O (2.423 g), 9 mmol Co(NO 3 ) 2 6H 2 O (2.619 g) were dissolved in 10 mL of ethanol aqueous solution (V 乙醇 :V H2O =1:3), to obtain mixed solutions respectively;
[0046] (2) 0.02 g of cetyltrimethylammonium bromide (CTAB) surfactant was dissolved in 50 mL of anhydrous ethanol and magnetically stirred at 600 rpm for 3 h to obtain solution A;
[0047] (3) 9 mmol of trimesic acid (TMA) (1.89 g) was dissolved in 300 mL of deionized water and stirred magnetically at 600 rpm for 60 min. At the same time, a 2 M aqueous solution of NaOH was added dropwise to adjust the pH to 7.0 to obtain solution B.
[0048] (4) The mixed solution obtained in step (1) was magnetically stirred at 500 rpm for 30 min to obtain a solution C;
[0049] (5) Solution A was added dropwise to solution C at a rate of 5 mL / min, and magnetic stirring was performed at 600 rpm for 30 min until the reactants were completely mixed to obtain solution D;
[0050] (6) Solution D was added dropwise to solution B at a rate of 10 mL / min, and magnetically stirred at 800 rpm for 12 h. During this process, a pink MOFs product was generated, precipitated, and collected. The product was first washed with an ethanol aqueous solution with a volume fraction of 80%, centrifuged at 8000 rpm, and the process was repeated 3 times. Then, it was washed with deionized water and centrifuged at 8000 rpm, and the process was repeated 5 times. After drying at 110 ° C in vacuum (vacuum degree of 50 Pa) for 48 h, TM-MOFs precursor was obtained.
[0051] S2. Preparation of composite hydrogen storage material: 0.5 g TM-MOFs precursor obtained in step S1 was pre-milled at 150 rpm for 4 h, and 4.5 g MgH 2 The powder material was ball-milled at 300 rpm for 8 h, and the ball-milled mixture was placed in a vacuum environment and kept at 150 °C for 4 h. Then, the temperature was raised to 450 °C in a vacuum environment and kept for 2 h to completely dehydrogenate to obtain the ternary TM-MOFs@MgH 2 Composite hydrogen storage materials.
[0052] Comparative Example 1 provides a pure MgH 2 Materials, which are purchased from Shanghai Meiyuan Power Technology Co., Ltd.
[0053] The effects of the composite materials provided in the above embodiments and comparative examples were verified by the following tests:
[0054] 1. The ternary transition metal TM-MOFs (TM = Fe, Co, Ni) precursor material in Example 1 was observed and characterized by scanning electron microscopy (SEM). The product morphology is as follows: Figure 1 shown.
[0055] Depend on Figure 1 It can be seen that the TM-MOFs (TM=Fe, Co, Ni) precursor material in Example 1 is a regular stick-like structure with a length of 20-30 μm.
[0056] 2. The ternary TM-MOFs@MgH 2 Materials and pure MgH provided in Comparative Example 1 2 The material was subjected to XRD test, and the results were as follows Figure 2 .
[0057] Depend on Figure 2 It can be seen that during the reaction, the Ni element in the ternary MOFs material forms metal clusters and reacts with Mg to form Mg in situ. 2 NeA 4 / Mg 2 Ni catalyzes the hydrogen storage system, while Fe and Co elements of the same molar mass form an intermetallic compound CoFe at high temperature, playing the role of an efficient nanocatalyst.
[0058] 3. The ternary TM-MOFs@MgH 2 The material was subjected to isothermal hydrogen absorption and desorption tests at temperatures of 598, 623 and 648 K, hydrogen pressure range: 0.01-3 MPa, equilibrium time 30 s, and the results are as follows: Figure 3 .
[0059] Depend on Figure 3 It can be seen that due to the improvement of kinetic performance, the hydrogen absorption and desorption platform is flat, and the maximum hydrogen storage capacity at each temperature can reach 5.2wt%.
[0060] 4. The ternary TM-MOFs@MgH 2 The material was tested by differential scanning calorimetry, and the results were as follows Figure 4 .
[0061] Depend on Figure 4 It can be seen that at a heating rate of 10K / min, the peak dehydrogenation temperature of the composite material is significantly reduced to 549.9K due to the action of the nano-multi-catalyst, which is much lower than the dehydrogenation peak temperature (703K) of pure magnesium hydride at the same heating rate, indicating that the multi-catalytic system has a significant effect on its kinetics.
[0062] 5. Ternary TM-MOFs@MgH provided in Example 1 2 The material is based on the DSC curve obtained from the test. p 2 )vs.1000 / T p The fitting result graph is as follows: Figure 5 .
[0063] Depend on Figure 5 It can be seen that the dehydrogenation activation energy of the system increases from 180 kJ / mol H 2 Reduced to 98.1 kJ / molH 2.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a ternary TM-MOFs@MgH2 composite hydrogen storage material, characterized in that: The steps include: S1. Preparation of ternary transition metal TM-MOFs precursor: (1) Dissolving Ni, Fe and Co in the form of nitrates in ethanol aqueous solution to obtain metal ion mixed solutions; (2) The surfactant is dissolved in anhydrous ethanol and stirred at 300-1000 rpm for 3 h to obtain solution A; (3) The organic ligand is dissolved in deionized water and stirred at 300-1000 rpm for 20-60 min. At the same time, a 2 M alkaline solution is added dropwise to adjust the pH value to obtain solution B. (4) Stirring the mixed solution obtained in step (1) at a speed of 200-800 rpm for 20-60 min to mix evenly to obtain solution C; (5) Solution A was added dropwise to solution C at a rate of 5 mL / min, and stirred at 500-800 rpm for 30 min until the reactants were completely mixed to obtain solution D; (6) Add solution D to solution B dropwise at a rate of 10 mL / min, stir at 400-1200 rpm for 6-48 h, collect the reaction precipitate, wash, centrifuge, and dry to obtain a TM-MOFs precursor; S2. Preparation of composite hydrogen storage material: pre-ball milling the TM-MOFs precursor obtained in step S1, adding MgH2 powder material, ball milling composite, placing the ball-milled mixture powder in a vacuum environment for complete dehydrogenation, and obtaining a ternary TM-MOFs@MgH2 composite hydrogen storage material; The transition metals TM are Ni, Fe and Co respectively.
2. The preparation method according to claim 1, characterized in that: In step S1 (2), the surfactant includes one or more of hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, octadecyldimethylhydroxyethylammonium nitrate, and tetrabutylammonium chloride.
3. The preparation method according to claim 1, characterized in that: In step S1 (3), the pH value of the solution is adjusted to 7.
0.
4. The preparation method according to claim 1, characterized in that: The cleaning and centrifugation treatment in step S1 (6) is as follows: first, the sample is cleaned with an ethanol aqueous solution having a volume fraction of 80%, and then centrifuged at 8000 rpm, and this process is repeated 3-5 times; then, the sample is cleaned with deionized water, and then centrifuged at 8000 rpm, and this process is repeated 3-5 times.
5. The preparation method according to claim 1, characterized in that: In step S1 (6), the drying treatment is carried out at 80-130° C. for 24-72 h under a vacuum degree not exceeding 50 Pa to obtain a TM-MOFs precursor.
6. The preparation method according to claim 1, characterized in that: The pre-milling conditions in step S2 are: a rotation speed of 100-200 rpm and a time of 1-4 h.
7. The preparation method according to claim 1, characterized in that: The ball milling conditions in step S2 are: rotation speed of 150-300 rpm, and time of 4-8 h.
8. The preparation method according to claim 1, characterized in that: In step S2, the ball-milled mixture powder is placed in a vacuum environment and kept at 150° C. for 3-6 hours, and then heated to 450° C. in a vacuum environment and kept for 2 hours to completely dehydrogenate.
9. The ternary TM-MOFs@MgH2 composite hydrogen storage material prepared by the preparation method according to any one of claims 1 to 8.